Design, Synthesis, Multifunctionalization and Biomedical Applications of Multifunctional Mesoporous Silica-Based Drug Delivery Nanosystems - Chen, Yu.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This thesis reports on essential advances in the design, synthesis and biomedical applications of multifunctional Mesoporous Silica Nanoparticles (MSNs). It provides several examples of multifunctional MSN-based drug delivery nanosystems and demonstrates successful synergistic cancer therapies combining MSNs and high-intensity focused ultrasound. The book will especially be of interest to researchers and graduate students in the fields of biomaterials, biology, chemistry, medicine and the life sciences who are working to develop new methods and technologies to combat cancer.
Keywords: Biomaterials; Cancer; Biomedical engineering; Biomaterials; Cancer Biology; Biomedical Engineering and Bioengineering